APLIKASI TERDISTRIBUSI MERUPAKAN SALAH SATU SOLUSI PENYAMPAIAN INFORMASI - Eka Putra Mahardika P (JURNAL MITRA MANAJEMEN, 2015)
AbstractInternet as a global computer network has proved easier for users to obtain informationand to communicate. Users can send and retrieve files, send messages, chat directly ordistribute or retrieve information. To disseminate information through the Internet, thereare some things that need to be addressed: the dissemination of information is up todate, visualize good data, the ease of accessing data and information. Thus requiredthe selection of appropriate technologies for the results efficiently and effectively.